(untitled) (Research, Society and Development, 2020)
In Brazil, dairy production is the second most important segment of the food industry, due to its nutritional and sensory characteristics. Lactic cultures are used in production technology to accentuate the flavor, aroma, texture, and acidity of dairy products that make them more acceptable to consumers. Therefore, the objective of this study was to evaluate the technological potential of species of the genus Enterococcus and strains of S. infantarius subsp. infantarius isolated from artisanal Coalho cheese from Paraíba, Brazil, to select them for the manufacture of fermented dairy products. The acidifying capacity, proteolytic activity, aroma production, β-Galactosidase activity, tolerance to sodium chloride, and antagonistic activity against different pathogens were evaluated. Of the strains analyzed, 26.67% were considered fast acidifiers, 33.33% were able to produce proteolytic enzymes, 26.67% showed β-galactosidase enzymatic activity and 33.33% were tolerant to sodium chloride. The pathogens are inhibited by 40.00% of the lactic acid bacteria (BAL) tested. The strains of Enterococcus showed higher values than the strains of S. infantarius subsp. infantarius, in particular the E. faecium KT990027 strain. Thus, we can conclude that E. faecium KT990027 can be used as a starter culture, as it presented the best general technological characteristics applicable to this type of culture. These results confirm that the artisanal Coalho cheese from Paraíba has BAL that can be used in the dairy industry.